Adverse childhood experiences and onset of migraine in Canadian adolescents: A cohort study. Issue 3 (5th February 2022) - Hammond, Nicole G.; Colman, Ian; Orr, Serena L.
Abstract: Background: Adverse childhood experiences (ACEs) are cross‐sectionally associated with headache, including migraine, in pediatric populations. Objective: The objective of this study was to determine whether ACEs are prospectively associated with incident health‐professional diagnosed migraine and prevalence of non‐migraine frequent headache in adolescence, either directly or indirectly through symptoms of depression and anxiety. Methods: We used data from the National Longitudinal Survey of Children and Youth, a Canadian cohort study that followed children aged 0/1 at baseline, and the person most knowledgeable about them (PMK) until the child reached adolescence. The PMK reported on 14 ACEs (e.g., parental death) when the child was 4/5 and 6/7 years, and symptoms of depression and anxiety in late childhood (age 8/9 years), using a validated tool. Migraine (primary outcome) was ascertained via PMK report of a health‐professional diagnosis, and non‐migraine frequent headache (>1 time per week) was adolescent self‐report, both measured at age 14/15. We estimated direct and indirect effects (IEs) on the log‐odds scale through symptoms of depression and anxiety (mediator). We adjusted for sex, parental migraine, and economic deprivation. The analytic sample sizes were: n  = 2058 (migraine) and n  = 1730 (frequent headache). Results: There were n unweighted  = 71 respondents with migraine (3.4%, 71/2058) and n unweighted  = 204 with non‐migraine frequent headache (11.8%, 204/1730). Most respondents experienced no ACEs (weighted percentage = 55.7), followed by 1 ACE (weighted percentage = 34.7) and greater than or equal to two ACEs (weighted percentage = 9.6), respectively. There were direct associations between experiencing one (odds ratio [OR] = 1.71, 95% confidence interval [CI]: 1.01–2.87) and equal to or greater than two (OR = 2.33, 95% CI: 1.13–4.80) ACEs and migraine, but not for non‐migraine frequent headache. There were no indirect relationships through symptoms of depression and anxiety for migraine (1 ACE: OR = 1.06, 95% CI: 0.99–1.13 and ≥2 ACEs: OR = 1.11, 95% CI: 0.98–1.28) or non‐migraine frequent headache (1 ACE: OR = 0.99, 95% CI: 0.95–1.03 and ≥2 ACEs: OR = 0.98, 95% CI: 0.90–1.07). Conclusions: ACEs may confer an increased risk of migraine onset in adolescence. The association was not explained by symptoms of depression and anxiety in late childhood.